Effects of Custodiol-N, a novel organ preservation solution, on ischemia/reperfusion injury - Loganathan, Sivakkanan; Radovits, Tamás; Hirschberg, Kristóf; Korkmaz-İçöz, Sevil; Koch, Achim; Karck, Matthias; Szabó, Gábor (The journal of thoracic and cardiovascular surgery, 2010)
Custodiol (histidine-tryptophan-ketoglutarate solution) is a leading organ preservation solution. On the basis of this solution, the novel Custodiol-N was developed. The present study investigated the effects of Custodiol-N in a rat model of heart transplantation.